Effects of Extracts of Feed Additives Including Rosemary (Rosmarinus officinalis) and Aloe Vera (Aloe barbadensis) on the Growth Performance and Feed Utility of Nile Tilapia (Oreochromis niloticus) - Ebru Yılmaz; Deniz Çoban; Birsen Kırım; Mehmet Güler (Turkish Journal of Agriculture: Food Science and Technology, 2019)
This study was performed to determine the effects of the extracts of two alternative antimicrobial agents that do not harm the ecosystem (rosemary, Rosmarinus officinalis and aloe vera, Aloe barbadensis) when added to the feed of tilapia (Oreochromis niloticus) on the growth performance, proximate composition, and biometric characteristics. Rosemary extract was added to the experimental diet in ratios of 0.1%, 0.25%, and 0.5% while aloe vera extract was added to the experimental diet in ratios of 0.5%, 1%, and 2.5%. After 90 days of the feeding trial, no change was seen in the weight increase, specific growth rate, feed conversion ratio, condition factor, hepatosomatic index, or viscerosomatic index of the tilapia. The fact that proximate analyses did not differ between groups showed that the plant extracts did not adversely affect the health status of tilapia in the ratios used in this study. As a result, the addition of 0.1%, 0.25%, and 0.5% rosemary extract and the addition of 0.5%, 1%, and 2.5% aloe vera extract to tilapia feeds did not cause changes in the growth performance, biometric indexes, or chemical composition findings of the fish meat.